2022
DOI: 10.1108/ijoem-07-2021-1164
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and SMEs' performance: mediating role of corporate image, corporate reputation and customer loyalty

Abstract: PurposeThe purpose of the paper is to evaluate the essential role of corporate social responsibility (CSR) on SMEs' performance by exploring the mediating role of corporate image (CI), corporate reputation (CR) and customer loyalty (CL) between CSR and firm performance (FP) in the context of an emerging country.Design/methodology/approachBased on an extended literature review on CSR, CI, CR and CL studies, the authors evaluate the impact of these four constructs on SMEs' performance in an emerging market. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 91 publications
5
81
0
12
Order By: Relevance
“…An argument can be made that GSCM does not improve performance because it takes time, experienced leadership support, and commitment to implement. Zainal et al (2022c) found the same thing, concluding that GSCM practices had no impact on environmental performance and development in the United Arab Emirates, a similar context (Le 2022). Because supply chains in crisis are more likely to wisely use their unique and uncommon internal resources when formulating strategies to achieve their competitive advantages, the GSC has little impact on sustainable performance.…”
Section: Discussionmentioning
confidence: 95%
“…An argument can be made that GSCM does not improve performance because it takes time, experienced leadership support, and commitment to implement. Zainal et al (2022c) found the same thing, concluding that GSCM practices had no impact on environmental performance and development in the United Arab Emirates, a similar context (Le 2022). Because supply chains in crisis are more likely to wisely use their unique and uncommon internal resources when formulating strategies to achieve their competitive advantages, the GSC has little impact on sustainable performance.…”
Section: Discussionmentioning
confidence: 95%
“…Government subsidy further strengthens the negative relationship between CSR and firm performance. In countries where the relationship between SME CSR performance and financial performance is positive [42,43,[56][57][58][59], CSR expenditure could bring more benefits, rewards, and competitive advantages to firms. In this vein, CSR involvement is not regarded as an extra burden to SMEs, but rather as a long-term investment that contributes to sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in the context of SME CSR and firm performance, most results show positive results given the closer relationships between SMEs and their stakeholders. For instance, Choongo [43], Ikram et al [42], Thanh [56], Torugsa et al [57], Turyakira et al [58], Wentzel et al [59] all found positive and significant relationships between SME CSR activities and firm performance. Martinez-Conesa et al [60] also drew the conclusion that CSR initiatives positively impact firm performance through an analysis of 552 Spanish firms.…”
Section: Studies On Sme Csr Firm Performance and In The Context Of Ch...mentioning
confidence: 99%
“…If stakeholders do not believe in a company's CSR credentials, the two can have a negative relationship (Meseguer-Sánchez et al, 2021). Communications on corporate social responsibility can be seen as either positive or negative depending on stakeholders' perceptions (Collier and Esteban, 2007;Agyemang and Ansong, 2017;Le, 2022;respectively). H10: People's opinions regarding online CSR communications are influenced by the relevance of their presented material.…”
Section: Attitudes Toward Csr Communicationsmentioning
confidence: 99%